Selected Methods of Balanced Incomplete Sequence Crossover Designs - L., Adebara; K, Muhammad; A. J., Rotipin (Covenant Journal of Physical and Life Sciences, 2021)
Crossover design is a design in which sequences receive different treatments one at a time at another period. Three construction methods of Balanced Incomplete Sequence Crossover Design (BISCOD) are selected for review in this paper. The first and third methods used the primitive root of every non-zero element of the multiplicative root, the prime number of treatment, and the second method used Balanced Incomplete Block Design (BIBD) for construction of any number of treatments, either prime or non-prime. Results show that each treatment is preceded by each other treatment once for both first and third methods, and for the second method, each treatment is preceded by each other treatment once and itself an unequal number of times. The conclusion shows that both first and third are used to construct a design for the prime number of treatments, while the second method constructs design for any whole number.